Peningkatan Hasil Belajar Matematika Dengan Menggunakan Model Pembelajaran Cooperative Script - Rulianna Sitorus (JURNAL PENA EDUKASI, 2018)
Abstract: This study aims to improve student learning outcomes by using Cooperative Script learning model on the subjects of Mathematics materials Fractional Operation Count in class VI SD Negeri 017129 Silomlom academic year 2016/2017. The subjects of this study are all students of class VI which amounted to 10. While the object of this research is the result of student learning on subjects of Mathematics materials and Simple Roots with the application of Cooperative Script learning model. Data collection tools using observation and tes.Pada pretest obtained test results of student learning on Fractional Counting Operation materials that is with an average value of 47 and percentage of classical completeness 20% (2 students). After applied Cooperative Script learning model on the first cycle obtained the level of achievement of student learning outcomes reached an average value of 66 with a percentage of 50% (5 students). While on the second cycle obtained the level of achievement of learning achieves an average score of 83 with a percentage of student completeness of 90% (9 students). Thus it can be concluded that by using Cooperative Script learning model on the learning process can improve student learning outcomes when applied to the subject of Mathematics with Materials Counting Fractions in Class VI SD Negeri 017129 Silomlom academic year 2016/2017. Keyword: cooperative script, fractional, rank, root Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa dengan menggunakan model pembelajaran Cooperative Script pada mata pelajaran Ma-tematika materi Operasi Hitung Pecahan di kelas VI SD Negeri 017129 Silomlom tahun pelajaran 2016/2017. Subjek penelitian ini adalah seluruh siswa kelas VI yang berjumlah 10. Sedangkan objek penelitan ini adalah hasil belajar siswa pada mata pelajaran Matematika materi Perpangkatan dan Akar Sederhana dengan penerapan model pembelajaran Cooperative Script. Alat pengumpulan data menggunakan observasi dan tes.Pada pretest awal diperoleh tes hasil belajar siswa pada materi Operasi Hitung Pecahan yaitu dengan nilai rata-rata 47 dan presentase ketuntasan klasikal 20% (2 siswa). Setelah diterapkan model pembelajaran Coop-erative Script pada siklus I diperoleh tingkat pencapaian hasil belajar siswa mencapai nilai rata-rata 66 dengan presentase 50% (5 siswa). Sedangkan pada siklus II diperoleh tingkat pencapaian hasil belajar mencapai nilai rata-rata 83 dengan presentase ketuntasan siswa sebesar 90% (9 siswa). Dengan demikian dapat disimpulkan bahwa dengan menggunakan model pembelajaran Cooperative Script pada proses pembelajaran dapat meningkatkan hasil belajar siswa bila diterapkan pada pelajaran Matematika dengan materi Operasi Hitung Pecahan di Kelas VI SD Negeri 017129 Silomlom Tahun Pelajaran 2016/2017. Kata kunci: cooperative script, pecahan, pangkat, akar